Perbandingan Kinerja Keuangan PT. HM Sampoerna Tbk Sebelum dan Sesudah Akuisisi Menggunakan Metode Financial Value Added (FVA) dan Market Value Added (MVA) - Nurdianto, Tri Heri (BISMA (Bisnis dan Manajemen), 2018)
Financial performance measurement within companies is very essential to make a policy about evaluation process of a company. Most research about company's financial performance in the past was measured by traditional accounting methods (financial ratios). Unfortunately, financial performance measurement using accounting method has a weakness for ignoring the cost of capital invested by investors. Financial Value Added (FVA) method is a measure of financial performance of companies that aims to evaluate financial value of the company, while the Market Value Added (MVA) method is a measure of financial performance of companies that aims to identify the value added of companies by analyzing the external conditions. This research was conducted to compare financial performance before and after acquisition using FVA and MVA. The data is processed using the program Microsoft office excel 2007. The results of this study implies, that there are differences in financial performance as measured by the method of FVA and MV. It was shown that the average value of FVA after the acquisition is greater than value of FVA before the acquisition, while the average value after the acquisition of MVA is greater than MVA before the acquisition. The result shows different conclusion between the FVA and the MVA, because there are differences approach about those two measurements.FVA is a method to measure financial performance which is influenced by sales and money invested by the company. The more money invested by the company, the value of FVA become smaller. On the contrary, MVA is a method to measure financial performance which is influenced by a company's stock price. The higher closing price of a company, the bigger MVA